Systematic Literature Review: Model Pembelajaran untuk Meningkatkan Kemampuan Literasi Matematika Siswa - Juniar, Berlian Bella; Meiliasari; Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2025)
Mathematical literacy is the mathematical ability that requires critical reasoning skills and problem-solving logic, in order to solve everyday problems. Several environmental factors can influence a person's mathematical literacy, including the use of learning models in the teaching and learning process. The Systematic Literature Review (SLR) method was used in this research to find and analyze various relevant studies to answer the Research Question (RQ). Data were collected through the review of national and international articles from the Google Scholar and Sinta databases. The results show that the Problem-Based Learning model is the most frequently used model to improve students' mathematics skills from 2019 to 2024. By applying the Problem-Based Learning model, students' mathematical literacy skills significantly increased. This model helps students learn to think critically, and analytically, and solve mathematical problems in real-world contexts. Overall, this model enhances students' understanding and application of mathematical concepts.